Mediasi Penal dalam Penyelesaian Tindak Pidana Kekerasan dalam Rumah Tangga yang Dilakukan Suami Terhadap Istri (Studi di Polres Pamekasan) - Agung Fakhruzy (Fakultas Syariah Univeritas Islam Madura, 2021)
This Journal writing is about the penal mediation in the resolution of criminal offenses related to domestic violence against the husband and wife who performed at the police station Pamekasan This background Basically every family wants to build a happy family and a sense of mutual love, both physically and spiritually, but the fact that not all families desire is reached, where the frequent occurrence of domestic violence committed by husbands against wives, but in cases of litigation pending against domestic violence in the penal mediation solved by investigators, as is done in the Police Pamekasan where investigators penal mediation in cases of domestic violence. Thus, the observed phenomenon needs to be studied on a few things, first: basic considerations Pamekasan police, victims and perpetrators of domestic violence penal mediation to resolve cases of domestic violence, and the second: is related to the implementation of penal mediation in resolving criminal offenses relating to the violence in the household.